Situation Report: Poland, 19 March 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Party's Draft Program Government Offensive against "Freedom and Peace" Continues Financing the Underground / by Michal Kolodziej Statistics on the Underground Press The Extended Working Week Controversy Miscellaneous Items